Absolute structure determination of Berkecoumarin by X-ray and electron diffraction - Decato, Daniel; Palatinus, Lukáš; Stierle, Andrea; Stierle, Donald (Acta crystallographica. Section C, Structural chemistry, 2024)
X-ray and electron diffraction methods independently identify the S-enantiomer of Berkecoumarin [systematic name: (S)-8-hydroxy-3-(2-hydroxypropyl)-6-methoxy-2H-chromen-2-one]. Isolated from Berkeley Pit Lake Penicillium sp., Berkecoumarin is a natural product with a light-atom composition (C13H14O5) that challenges in-house absolute structure determination by anomalous scattering. This study further demonstrates the utility of dynamical refinement of electron-diffraction data for absolute structure determination.
Keywords: crystal structure; natural product; chromenone; absolute structure determination; Berkecoumarin; microED; dynamical refinement; coumarin; electron diffraction